2009
DOI: 10.4315/0362-028x-72.4.860
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Destruction of Escherichia coli O157:H7 in Sous-Vide Cooked Ground Beef as Affected by Tea Leaf and Apple Skin Powders

Abstract: We investigated the heat resistance of a four-strain mixture of Escherichia coli O157:H7 in raw ground beef in both the absence and presence of white and green tea powders and an apple skin extract. Inoculated meat was cooked using the sous-vide technique, i.e., the meat was packaged in sterile bags and completely immersed in a circulating water bath at low temperature for a period of time. The bags were cooked for 1 h to an internal temperature of 55, 58, 60, or 62.5 degrees C, and then held from 240 min at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Tailing has been attributed to the presence of a few large clumps of cells or a more heattolerant subspecies of cells (19,25,35). To account for deviations from first order kinetics, researchers have obtained D-values from the linear portion of the curve (2,21,52) or have used mathematical models to address nonlinearity (5,12,22,23). Although mathematical models are helpful for predicting the death rate of microbial populations, they have limitations when determining thermal death parameters (26).…”
Section: Resultsmentioning
confidence: 99%
“…Tailing has been attributed to the presence of a few large clumps of cells or a more heattolerant subspecies of cells (19,25,35). To account for deviations from first order kinetics, researchers have obtained D-values from the linear portion of the curve (2,21,52) or have used mathematical models to address nonlinearity (5,12,22,23). Although mathematical models are helpful for predicting the death rate of microbial populations, they have limitations when determining thermal death parameters (26).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that apple extract containing apple polyphenols enhances heat inactivation of E. coli O157:H7 in ground beef as well as reduces the biological activity of Staphylococcus enterotoxin A (14,21). Polyphenols found in red and white wine, in combination with other natural antimicrobial agents such as those found in garlic juice and oregano leaves, were found to have high antimicrobial activity against strains of B. cereus in wine marinades (9).…”
Section: Resultsmentioning
confidence: 99%
“…These authors reported that the addition of NaCl (0 to 3%) in ground beef had no effect on z-values of L. monocytogenes; however, the addition of NaCl in the presence of 3% apple polyphenols resulted in lower z-values. Regarding the effect of green tea extract on z-values, Juneja et al (19) reported an increase in z-values of E. coli 0157:H7 in beef from 4.23°C (beef with no additive) to 5.06°C (beef with 3% green tea extract). The inconsistent results between the former study by Juneja et al (19) and the present study may be attributed to different substrates and different bacterial species, exhibiting varying degrees of lag phases when exposed to heat to assess lethality at different temperatures.…”
Section: °Cmentioning
confidence: 99%